PSYCHOLOGICAL AND LINGUISTIC BASICS LITERACY TEACHING METHODS SIX-YEAR-OLD FIRST GRADES - Kravtsova, I.A.; Poddubnyak, O. (Pedagogy of Higher and Secondary Education, 2022)
This article deals with the questtion about the development of speech and mental activity б year old children at lessons of studing grammar material in the ABC period and also peculierities of psycological and linguistical raund of methodics of studing grammar offirst form pupils.